Effect of surface roughness on helicopter main rotor blade - Wan Rohizan, Wan Norhafizan (2017)
This study describes the effect of surface roughness when applied on helicopter main rotor blade. The study was performed in wind tunnel using scaled helicopter model to study the aerodynamic characteristic in vertical flight condition. This is to show the feasibility of surface roughness for rotary wing applications. The requirement for helicopter main rotor blades are high thrust and low power requirement. Smooth profile of main rotor blade is modified by applying surface roughness on the upper and lower camber in transition and turbulent boundary layer region; starting from 25% of chord length and gradually extended to trailing edge (TE). The analysis following the research shows that with right application of roughness will result in lower power requirement. The aerodynamic efficiency is enhanced at lower and upper pitch level between 7% to 69%. However, this came at the expense of reduced thrust at middle collective pitch level between 11% to 45%. Surface roughness found to have insignificant effect on rotor power requirement (only 2% to 5% difference). At upper range of collective pitch level, surface roughness is seen to delay the stall angle as well as increasing the lift in the stall region. Meanwhile for aerodynamic efficiency, thrust-to-power ratio shows less steep graph and peak ratio were pushed to higher pitch level. This indicates wider operating envelope and more predictable flight profile. All these results may provide foundation for further research to further optimisation of surface roughness effect for rotary wing aircraft.